Airway Smooth Muscle Regulated by Oxidative Stress in COPD - Hiroaki Kume; Ryuki Yamada; Yuki Sato; Ryuichi Togawa (MDPI AG, 2023)
Since COPD is a heterogeneous disease, a specific anti-inflammatory therapy for this disease has not been established yet. Oxidative stress is recognized as a major predisposing factor to COPD related inflammatory responses, resulting in pathological features of small airway fibrosis and emphysema. However, little is known about effects of oxidative stress on airway smooth muscle. Cigarette smoke increases intracellular Ca2+ concentration and enhances response to muscarinic agonists in human airway smooth muscle. Cigarette smoke also enhances proliferation of these cells with altered mitochondrial protein. Hydrogen peroxide and 8-isoprostans are increased in the exhaled breath condensate in COPD. These endogenous oxidants cause contraction of tracheal smooth muscle with Ca2+ dynamics through Ca2+ channels and with Ca2+ sensitization through Rho-kinase. TNF-α and growth factors potentiate proliferation of these cells by synthesis of ROS. Oxidative stress can alter the function of airway smooth muscle through Ca2+ signaling. These phenotype changes are associated with manifestations (dyspnea, wheezing) and pathophysiology (airflow limitation, airway remodeling, airway hyperresponsiveness). Therefore, airway smooth muscle is a therapeutic target against COPD; oxidative stress should be included in treatable traits for COPD to advance precision medicine. Research into Ca2+ signaling related to ROS may contribute to the development of a novel agent for COPD.